2021
DOI: 10.3390/nu13041044
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Pregnancy Diet Quality Is Associated with Lowering the Risk of Offspring Obesity and Underweight: Finding from a Prospective Cohort Study

Abstract: Maternal diet plays a critical role in epigenetic changes and the establishment of the gut microbiome in the fetus, which has been associated with weight outcomes in offspring. This study examined the association between maternal diet quality before pregnancy and childhood body mass index (BMI) in offspring. There were 1936 mothers with 3391 children included from the Australian Longitudinal Study on Women’s Health (ALSWH) and the Mothers and their Children’s Health (MatCH) study. Maternal dietary intakes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Several studies have been conducted to evaluate the roles of parental lifestyle factors on obesity in offspring, demonstrating that parental obesity was associated with a higher risk of obesity in offspring [15,39]. Conversely, few studies examined the role of parental diet in offspring obesity, and were primarily conducted before or during pregnancy; they suggested that adherence to a better maternal diet was associated with a reduced risk of obesity in childhood [40][41][42]. We found that normal BMI and diverse dietary intake in parents, especially fathers, were associated with a lower risk of offspring obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the roles of parental lifestyle factors on obesity in offspring, demonstrating that parental obesity was associated with a higher risk of obesity in offspring [15,39]. Conversely, few studies examined the role of parental diet in offspring obesity, and were primarily conducted before or during pregnancy; they suggested that adherence to a better maternal diet was associated with a reduced risk of obesity in childhood [40][41][42]. We found that normal BMI and diverse dietary intake in parents, especially fathers, were associated with a lower risk of offspring obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 study 14 reported paternal overweight or obesity as risk factor for childhood obesity. 4 observational studies [15][16][17][18] focused on the associations of maternal lifestyle factors during preconception with childhood obesity risk. 2 observational studies 15,16 showed that maternal smoking in the preconception period was associated with an increased risk of childhood obesity, whereas no associations with the risk of childhood obesity were reported for maternal preconception diet 15,17 or physical activity 15,18 .…”
Section: Risk Factors For Childhood Obesity In Preconceptionmentioning
confidence: 99%
“…The Healthy Eating Index (HEI) is a diet quality measure used to assess how well a set of foods aligns with key recommendations of the Dietary Guidelines for Americans ( 5 ). HEI can quantitatively assess the diet quality of various human groups and examine the prospective and cross-sectional links of diet quality with health outcomes, such as offspring overweight ( 6 ), risk for all-cause mortality of cardiovascular diseases and cancers ( 7 ), and depression ( 8 ). HEI-2015 as the most current version meets the main recommendations of the 2015–2020 Dietary Guidelines for Americans ( 5 ).…”
Section: Introductionmentioning
confidence: 99%